Hepatoprotective effect of the root extract of green tea against malathion-induced oxidative stress in rats - Negar Mehri; Hamed Felehgari; Amir Larki Harchegani; Hamid Behrooj; Nejat Kheiripour; Hassan Ghasemi; Mahmoud Mirhoseini; Akram Ranjbar (Shahrekord University of Medical Sciences, 2016)
Introduction: Organophosphorus (OPs) pesticides such as malathion intoxication has been shown to generate oxidative stress due to the production of free radicals and alteration of the antioxidant defense system. The aim of this study was to evaluate the effects of extracts from green tea (GT) hydroalcoholic extract on liver function. Methods: Male Wistar rats were separated into 4 groups of 8 rats each. Group I (control), group II was given GT (10 mg/kg/day). Animals of groups III received only malathion, group IV was given GT+ malathion. Animals received malathion 150 mg/kg by gavage and GT 30 mg/kg for 1 week through intraperitoneal injection. Twenty-four hours after treatment, blood samples were collected. Alanine aminotransferase (ALT), aspartate aminotransferase (AST) concentrations as well as biomarkers of oxidative stress such as lipid peroxidation (LPO), total antioxidant capacity (TAC) and total thiol groups (TTG) were measured. Results: A decrease in ALT and AST levels in GT group were observed compared with the ones in control group. Also, the results showed that malathion could increase liver toxicity in rats through reduction of ALT and AST. Conclusion: Amelioration of malathion toxicity through reduction of inflammation may suggest a prolonged therapeutic option against pesticides-induced hepatotoxicity.